The significance of online technologies in teaching English communication - Pakirdinova Sharofat Abdumutaljonovna, Bozorboyeva Xusnidaxon Bahromjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This work presents contemporary ways of teaching knowledge with the help of online technologies, benefits and some disadvantages of using them and impact of online technology on students’ academic performance.